Accurate Detection of Rifampicin-Resistant Mycobacterium Tuberculosis Strains - Keum-Soo Song; Satish Balasaheb Nimse; Hee Jin Kim; Jeongseong Yang; Taisun Kim (Sensors, 2016)
In 2013 alone, the death rate among the 9.0 million people infected with Mycobacterium tuberculosis (TB) worldwide was around 14%, which is unacceptably high. An empiric treatment of patients infected with TB or drug-resistant Mycobacterium tuberculosis (MDR-TB) strain can also result in the spread of MDR-TB. The diagnostic tools which are rapid, reliable, and have simple experimental protocols can significantly help in decreasing the prevalence rate of MDR-TB strain. We report the evaluation of the 9G technology based 9G DNAChips that allow accurate detection and discrimination of TB and MDR-TB-RIF. One hundred and thirteen known cultured samples were used to evaluate the ability of 9G DNAChip in the detection and discrimination of TB and MDR-TB-RIF strains. Hybridization of immobilized probes with the PCR products of TB and MDR-TB-RIF strains allow their detection and discrimination. The accuracy of 9G DNAChip was determined by comparing its results with sequencing analysis and drug susceptibility testing. Sequencing analysis showed 100% agreement with the results of 9G DNAChip. The 9G DNAChip showed very high sensitivity (95.4%) and specificity (100%).